A field strength self-adapting alkali-free enamel solder paste composition with bistable electrical response and a preparation method and application thereof

CN123003147APending Publication Date: 2026-10-30HUNAN ZONGCHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611175205.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

1、击穿阈值固化且不可逆:传统绝缘材料的体击穿或沿面闪络场强是固定的物理常数,一旦瞬态电压超过其临界点,材料内部晶格立即发生不可逆的破坏性击穿,形成热熔洞或微裂纹,导致设备永久性报废,无法满足核聚变装置及加速器等长寿命、高可靠性装备的运维要求

Benefits of technology

本发明所述的一种具有双稳态电响应的场强自适应型无碱搪瓷焊膏组合物,通过精密的无碱玻璃网络结构设计、稀土协同掺杂改性以及压敏功能填料的晶界势垒工程,使材料在常规工作电压区间(例如<100kV)保持极高的体积电阻率(>1014Ω·cm)和介电强度;而当瞬态超高压(例如>500kV或MV级脉冲)触发时,材料内部势垒发生雪崩式突变,产生均匀的体效应隧道电流或沿面弱导通,瞬间拉平过高的电位梯度,将破坏性能量转化为可控的焦耳热或位移电流,待脉冲消退后材料自动恢复高阻绝缘态;本特性从根本上解决了高压电力电子器件的“脉冲溃坝”问题,为极端电物理场景下的绝缘防护提供了全新的材料解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003147A_ABST
    Figure CN123003147A_ABST
Patent Text Reader

Abstract

The application discloses a field-strength self-adaptive alkali-free enamel solder paste composition with a bistable electric response, a preparation method and application thereof, and belongs to the technical field of special inorganic non-metallic materials and high-voltage power electronic packaging. The application constructs a barium-boron-silicon-zinc-aluminum basic glass system without any monovalent metal elements, and introduces high-content fluorides and rare earth oxides for synergistic modification, effectively improves the polymerization degree and thermal stability of the glass network structure, and eliminates the migration and degradation risk of alkali metal ions under high temperature and strong electric field from the root. At the same time, by compounding the surface interface engineering modified pressure-sensitive conductive functional fillers in the solid powder component, the intelligent switching function of material normal insulation and transient conduction is realized by using the nonlinear conductive mechanism of the fillers under strong electric field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary field of special inorganic non-metallic materials and high-voltage power electronic packaging. It relates to a field strength adaptive alkali-free enamel solder paste composition with bistable electrical response, its preparation method, and its application. Specifically, it relates to a composite enamel solder paste composition for extreme transient overvoltage protection, which is particularly suitable for demanding scenarios such as controlled nuclear fusion devices, ultra-high voltage flexible DC transmission converter valves, medical heavy ion accelerators, and rail transit traction converters that require simultaneous normal high voltage insulation and transient ultra-high voltage adaptive conduction. Background Technology

[0002] As pulsed power technology, ultra-high voltage power transmission and transformation, and nuclear fusion magnetic confinement devices continue to evolve towards miniaturization and high energy density, the electric field stress borne by the internal insulation components of these devices is escalating dramatically. Taking the magnet feeder systems in the International Thermonuclear Experimental Reactor (ITER) and the China Fusion Engineering Experimental Reactor (CFETR) as examples, their high-voltage feed windows must withstand the impact of nanosecond pulses reaching the MV level during the moment of superconducting magnet quench failure. Meanwhile, the damping capacitors and saturated reactor insulation supports in the converter valves of ultra-high voltage flexible DC transmission systems are constantly subjected to repeated attacks from operational overvoltages and lightning surges. Traditional high-voltage insulating enamel (ceramic glaze) or polymer materials reveal three inherent and insurmountable technical defects when facing such extreme transient overvoltages: 1. The breakdown threshold is fixed and irreversible: The volume breakdown or surface flashover field strength of traditional insulating materials is a fixed physical constant. Once the transient voltage exceeds its critical point, the internal lattice of the material will immediately undergo irreversible destructive breakdown, forming thermal holes or microcracks, resulting in permanent scrapping of the equipment. This cannot meet the operation and maintenance requirements of long-life and high-reliability equipment such as nuclear fusion devices and accelerators.

[0003] 2. Dielectric constant and impedance mismatch: In multilayer composite electrode structures, there is a sudden change in dielectric constant at the interface between the traditional insulating layer and the metal conductor, which can easily cause local electric field distortion, leading to tip discharge and partial discharge (PD) aging phenomena. This aging effect will significantly shorten the equipment life and increase the risk of unplanned shutdowns during the long-term operation of UHV converter valves.

[0004] 3. Lack of "field strength self-adaptation" capability: Existing materials cannot identify the essential difference between "normal working high voltage" and "dangerous transient ultra-high voltage". When a transient surge occurs, the material can only passively withstand it and cannot actively participate in the energy dissipation or electric field homogenization process, let alone have voltage clamping or surge discharge functions. This is seriously contrary to the urgent need for "active protection" type insulation materials in future smart grids and high-energy physics equipment.

[0005] Therefore, developing a field strength adaptive alkali-free enamel solder paste composition with bistable electrical response is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response, its preparation method, and its applications. This invention constructs a barium-boron-silicon-zinc-aluminum base glass system free of any monovalent metal elements and introduces high levels of fluorides and rare earth oxides for synergistic modification, effectively improving the polymerization degree and thermal stability of the glass network structure. This fundamentally eliminates the risk of migration and degradation of alkali metal ions under high temperatures and strong electric fields. Simultaneously, by compounding surface-interface engineering modified varistor fillers into the solid powder components, and utilizing their nonlinear conductivity mechanism under strong electric fields, the invention achieves intelligent switching between normal insulation and transient conduction.

[0007] The purpose of this invention is to provide a field strength adaptive alkali-free enamel solder paste composition with bistable electrical response.

[0008] Another objective of this invention is to provide a method for preparing the above-mentioned enamel solder paste composition, which ensures the homogeneous composite of glass powder and functional filler, as well as the batch stability of solder paste product performance through processes such as sealed melting, programmed annealing, precision grading and vacuum degassing and stirring.

[0009] Another object of the present invention is to provide applications of the above-mentioned enamel solder paste composition, particularly suitable for the encapsulation and protection of high-end equipment such as the insulating base of the feeder of the controlled nuclear fusion magnet, the voltage equalization coating of the casing of the damping capacitor of the ultra-high voltage converter valve, the insulating bracket of the high voltage modulator of the medical heavy ion accelerator, and the insulating heat dissipation substrate of the power module of the rail transit traction converter.

[0010] The objective of this invention is achieved through the following technical solution: A field strength adaptive alkali-free enamel solder paste composition with bistable electrical response, the solder paste composition being composed of solid components and an organic carrier, the organic carrier accounting for 15% to 30% of the total mass of the composition, and the solder paste composition containing no monovalent metal elements; The solid component comprises glass powder and varistor-sensitive conductive filler, and is made of the following components in weight percentage: Glass powder 55%–85%, varistor-sensitive conductive functional filler 15%–45%; The glass powder is a high-fluorine-content, alkali-free barium-based rare-earth synergistic glass system, composed of the following oxides by mass percentage: BaO 18%–28%, B2O3 25%–35%, SiO2 10%–16%, ZnO 5%–11%, Al2O3 3%–7%, La2O3 1.5%–4.5%, Y2O3 0.5%–3.0%, CeO2 0.5%–3.0%, Nd2O3 0%–2.5%, TiO2 0.5%–3.0%, CaF2 1.5%–4.0%, MgF2 1.0%–3.5%, AlF3 1.0%–3.5%. The pressure-sensitive conductive filler is a nano-zinc oxide-based pressure-sensitive material or silicon carbide whiskers with surface insulation treatment, and an average particle size D. 50 The range is 0.3μm to 6μm.

[0011] Furthermore, the organic carrier is composed of the following components in weight percentage: Ethyl cellulose resin 8%–18%, hydrogenated rosin resin 2%–8%, organic solvent 70%–88%, anti-settling agent 0.5%–2%; The organic solvent is one or more of diethylene glycol butyl ether acetate, terpineol, and dibutyl phthalate; the anti-settling agent is at least one of hydrogenated castor oil, modified bentonite, or polyamide wax.

[0012] Furthermore, the total fluorine content (calculated as F element) in the glass powder is 2.5wt% to 6.5wt%, and the content of total rare earth oxides La2O3+Y2O3+CeO2+Nd2O3 is 3.0wt% to 10.0wt%.

[0013] Furthermore, the solid component is made from the following components in mass percentage: 72% glass powder, 28% varistor-sensitive conductive filler; The glass powder is composed of the following oxides by mass percentage: BaO 24%, B2O330%, SiO213%, ZnO 8.5%, Al2O35%, La2O33.0%, Y2O32.0%, CeO22.0%, Nd2O31.5%, TiO22.0%, CaF23.0%, MgF22.5%, AlF32.5%; The pressure-sensitive conductive filler is a nano-zinc oxide co-doped with Bi, Sb, Co, and Mn, with an average particle size D. 50 It has a diameter of 1.5 μm and is covered with a SiO2 insulating layer with a thickness of 5 nm to 15 nm.

[0014] The field strength adaptive alkali-free enamel solder paste composition with bistable electrical response has the following sintering film performance indicators: Coefficient of linear expansion α (30℃~450℃): 6.8×10 -6 / ℃~8.2×10 -6 / ℃; Glass transition temperature Tg: 560℃~660℃; Normal volume resistivity (1kV test, 25℃): ≥1×10 14 Ω·cm; High-temperature volume resistivity (500℃): ≥5×10 11 Ω·cm; Trigger turn-on voltage threshold (V_breakdown, film thickness 100μm): 3.0kV~6.0kV adjustable; On-state resistance (@1.2×V_breakdown): ≤5×10 2 Ω; Pulse withstand capability (8 / 20μs lightning current wave): ≥50 impacts without breakdown or degradation; Vickers hardness: ≥6.0 GPa; Firing temperature range: 760℃~840℃; Coating / metal interface shear strength: ≥35 MPa.

[0015] This invention also relates to a method for preparing the above-mentioned field strength adaptive alkali-free enamel solder paste composition with bistable electrical response, comprising the following steps: S1. Selection and pretreatment of glass powder raw materials: Select oxide, fluoride and carbonate raw materials with a purity ≥99.5% according to the glass powder formula, and dry them at 200℃~300℃ for 2h~4h to remove adsorbed water and crystal water, and set them aside for later use. S2. Precise weighing and mixing of glass powder: Precisely weigh each raw material according to the glass powder formula, with a total weighing accuracy of ≤0.1%; place the weighed raw materials in a zirconia ball mill jar, add zirconia grinding balls, with a ball-to-material ratio of (2.5~3.5):1, dry ball milling for 3h~5h at a speed of 100rpm~150rpm, and after mixing, pass through a 120-mesh sieve to ensure no agglomeration; S3. Sealed melting of glass powder: The mixture obtained in S2 is loaded into a lidded platinum crucible or a high-purity corundum crucible. The crucible lid and body are sealed with high-temperature mullite sealant. The crucible is placed in a high-temperature electric furnace and heated to 1160℃~1240℃ at a rate of 8℃ / min~12℃ / min. The temperature is held for 1.5h~2.5h without stirring to avoid introducing air bubbles and impurities. After the holding time is completed, the crucible is quickly removed to obtain a homogeneous molten glass liquid. S4. Water quenching and annealing of molten glass: The molten glass in the crucible is quickly poured into deionized water for water quenching to obtain a glass frit; the glass frit is dried at 120℃~180℃ for 2h~3h, and then placed in an annealing furnace, heated to 485℃~535℃ at a rate of 2℃ / min~3℃ / min, held at that temperature for 1.5h~2.5h, and then slowly cooled to room temperature at a rate of 0.5℃ / min~1℃ / min to fully eliminate internal stress and obtain a glass frit; S5. Glass frit crushing and classification: The glass frit obtained in S4 is coarsely crushed to <5mm, and then placed in a planetary ball mill. Zirconia jar and zirconia balls are used, with a ball-to-material ratio of (5~7):1, a rotation speed of 200rpm~300rpm, and grinding for 3h~6h. Finally, the particle size distribution is controlled by an air classifier to obtain glass powder. S6. Pretreatment of varistor-conductive functional filler: Place commercially available or self-made nano zinc oxide-based varistor material or silicon carbide whiskers in a tube furnace and perform high-temperature oxidation treatment at 650℃~850℃ for 30min~90min in an oxygen or air atmosphere to form a dense high-resistance oxide layer (ZnO or SiO2) on its surface. Then cool, break up, and pass through a 200-mesh sieve to obtain the pretreated varistor-conductive functional filler. S7. Mixing of solid components: Weigh the glass powder obtained in S5 and the pretreated pressure-sensitive conductive functional filler obtained in S6 according to the solid component ratio, place them in a V-type mixer or a three-dimensional motion mixer, and mix for 40 min to 80 min to ensure that the two powders are evenly dispersed to obtain mixed solid powder. S8. Preparation of organic carrier: According to the formula of organic carrier, ethyl cellulose resin, hydrogenated rosin resin, anti-settling agent and organic solvent are added in sequence to a reaction vessel equipped with a stirrer and a reflux condenser. The mixture is heated in a water bath at 60℃~95℃ and stirred at a constant temperature for 1.5h~3h until all components are completely dissolved to form a clear and transparent homogeneous organic carrier. S9. Preparation of solder paste: The mixed solid powder obtained in S7 and the organic carrier obtained in S8 are placed in a double planetary vacuum stirrer and deaerator in proportion. Under the conditions of vacuum degree ≤ -0.095MPa and rotation speed of 600rpm~1200rpm, the mixture is stirred and mixed for 40min~90min to fully wet the solid powder and the organic carrier and form a uniform, stable, bubble-free paste, which is the field strength adaptive alkali-free enamel solder paste composition with bistable electrical response.

[0016] Furthermore, in S5, the coarse crushing of the glass frit obtained in S4 to <5mm is performed using a jaw crusher; the particle size distribution of the glass powder is controlled as follows: D 50 =2μm~7μm, D 10 ≥1.0μm, D90 ≤18μm; defective products are returned for re-grinding.

[0017] Furthermore, the nano-zinc oxide-based varistor material mentioned in S6 is a ZnO varistor powder co-doped with Bi2O3, Co2O3, MnO2, Sb2O3, and Cr2O3, with a total doping amount of 0.5 mol% to 6 mol.

[0018] Furthermore, the formation of a dense, high-resistance oxide layer on the surface described in S6 is achieved by coating the surface with a SiO2 insulating layer with a thickness of 5nm to 15nm. Specifically, for SiO2-coated nano-zinc oxide, a tetraethyl orthosilicate (TEOS) hydrolysis-condensation process can be used, reacting in an ethanol-water system at 50℃-70℃ for 4h-6h to achieve surface coating.

[0019] Furthermore, the viscosity of the solder paste composition described in S9 is 40 Pa·s to 180 Pa·s (Brookfield HBDV-II, CP51 rotor, 25°C, 5 rpm).

[0020] This invention also relates to the application of the above-mentioned field strength adaptive alkali-free enamel solder paste composition with bistable electrical response. The enamel solder paste composition is applied to the surface of the electrodes, insulating bases, or voltage equalization shielding rings of electronic components to be packaged by screen printing, dispensing, or casting. After debinding, sintering, and programmed cooling processes, a packaged solder joint, insulating coating, or sealing layer with field strength adaptive conduction function is formed. It is used for insulation protection and surge protection of the feeder insulation structure of controlled nuclear fusion magnets, the housing of damping capacitors of ultra-high voltage converter valves, the high voltage modulator bracket of medical heavy ion accelerators, and the power module substrate of rail transit traction converters.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response. Through precise alkali-free glass network structure design, rare-earth synergistic doping modification, and grain boundary barrier engineering of varistor functional fillers, the material maintains extremely high volume resistivity (>10) in the conventional operating voltage range (e.g., <100kV). 14 The material exhibits high resistance (Ω·cm) and dielectric strength. When triggered by transient ultra-high voltage (e.g., >500kV or MV-level pulses), the internal potential barrier of the material undergoes an avalanche-like abrupt change, generating a uniform volume effect tunneling current or weak surface conduction. This instantly flattens the excessively high potential gradient, converting the destructive energy into controllable Joule heating or displacement current. After the pulse dissipates, the material automatically returns to a high-resistance insulating state. This characteristic fundamentally solves the "pulse dam failure" problem of high-voltage power electronic devices, providing a brand-new material solution for insulation protection under extreme electrophysical scenarios. Attached Figure Description

[0022] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof.

[0023] Figure 1 A physical image of a dense composite enamel sintered film (formed by screen printing enamel solder paste prepared using the preparation method of a field strength adaptive alkali-free enamel solder paste composition with bistable electrical response in Example 1, followed by sintering at 820°C for 30 min under nitrogen atmosphere protection). Detailed Implementation

[0024] To make the technical solution, technical objectives, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments and comparative examples. All the following embodiments and comparative examples are based on the same preparation method, with differences only in the formulation of the glass powder in the solid components and the addition or non-addition of the varistor-conductive functional filler. However, it should be understood that these specific examples are only used to more clearly illustrate the core concept of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0025] First, to facilitate understanding of the key roles played by each component in the formulation of this invention, the functional mechanisms of each core component in the glass powder system of this invention will now be explained in detail: BaO is one of the core network modifiers in the glass system of this invention. 2+ With a large ionic radius and high polarizability, it can significantly improve the packing density of the glass network structure, thereby effectively blocking the migration of electrons and holes at high temperatures. This ensures that the material achieves ultra-high volume resistivity (≥5×10⁻⁶) at high temperatures. 11 BaO is a key cation (Ω·cm@500℃). Simultaneously, BaO can adjust the coefficient of thermal expansion of glass, enabling it to achieve good compatibility with commonly used metal substrates (such as Kovar alloys and stainless steel).

[0026] B2O3 is the primary glass network formant in this invention. Compared to the traditional SiO2 network, the [BO3]trigonal and [BO4] tetrahedral networks formed by B2O3 exhibit lower melting temperatures and higher dielectric strength. By controlling the B2O3 content within a relatively high range of 25% to 35%, this invention ensures good fluidity of the molten glass at 1160°C to 1240°C, while simultaneously providing ample non-bridging oxygen vacancies for the uniform solid solution of rare earth and fluoride ions.

[0027] The high fluoride content (CaF2, MgF2, AlF3) is one of the significant features that distinguishes this invention from existing technologies (including spark plug glazes mentioned in the background). In this invention, the total fluoride content is controlled at 2.5wt% to 6.5wt%, far exceeding that of conventional glazes (typically <2wt%). The introduction of fluoride ions has five core benefits: firstly, the electron cloud shielding effect—F... - It possesses extremely high electronegativity, which can further confine the transitions of free electrons in the glass network through the electron cloud shielding effect, significantly widening the intrinsic band gap and thus fundamentally improving the intrinsic volume resistivity of the material; secondly, network densification and cation pinning effect -- F - It is firmly embedded in the interstitial positions of the glass network structure in the form of halide-like ions, and effectively pins mobile cations (such as Ba) in the network by forming mixed anionic ligands such as [BO3F] and [AlO3F]. 2+ Zn 2+ Thirdly, process adaptation and a wide sintering window -- F - It can effectively break some bridging oxygen bonds in the glass network, reduce the viscosity of the high-temperature melt, and widen the sintering temperature window (760℃~840℃), which is beneficial for achieving densification sintering at lower temperatures; fourth, grain boundary pinning and barrier stabilization—appropriate amounts of fluorine ions can promote glass phase separation and form micro-nano-scale fluorine-rich droplets during sintering. These droplets can effectively pin grain boundaries after cooling, inhibiting excessive grain growth of nano-ZnO varistor fillers, thereby stabilizing their grain boundary barrier and ensuring pulse tolerance stability; fifth, the enhanced chemical bonding effect at the metal-ceramic interface—this is one of the most crucial innovative discoveries of this invention. During the high-temperature sintering stage, free active F - Ions are enriched at the wetting front between molten glass and a metal substrate (such as Kovar, stainless steel, or copper-based alloys), and are absorbed by metal cations (Fe) at the interface via chemisorption. 2+ Ni 2+ Cr 3+ An in-situ reaction generates a metal-fluorine (Me-Fx) chemically bonded transition layer with gradient composition characteristics. This transition layer improves the chemical compatibility between the molten glass and the metal, fundamentally changing the interface bonding mode of traditional enamel coatings that relies solely on physical embedding and mechanical locking. This significantly increases the interfacial shear strength between the coating and the substrate from less than 20 MPa in traditional systems to over 35 MPa, while also significantly reducing interfacial contact thermal resistance and interfacial polarization loss. This, in turn, synergistically improves the long-term reliability of the device under extreme thermal cycling conditions. These five effects work synergistically and are indispensable, collectively constituting the core technical logic of the high-fluorine content design of this invention.

[0028] The synergistic doping of rare earth oxides (La2O3, Y2O3, CeO2, Nd2O3) is another core element for achieving ultra-high insulation and mechanical strength in this invention. 3+ and Y 3+ It can enter the glass network as a network intermediate, and by abstracting non-bridging oxygen to form polyhedral coordination structures such as [LaO6] and [YO5], it significantly improves the crosslinking density and structural stability of the glass network. CeO2 contains Ce... 4+ / Ce 3+ The variable valence pairs can trap primary electrons injected from the electrode, forming deep-level traps that effectively suppress space charge accumulation, thereby delaying electrical aging and dendritic breakdown. The introduction of Nd₂O₃ further optimizes the matching degree between the dielectric constant and the coefficient of thermal expansion.

[0029] The varistor-sensitive conductive filler (nano-ZnO or SiC whiskers) is the key component for achieving the bistable electrical response in this invention. Under normal low-pressure conditions, the nano-ZnO coated with a SiO2 insulating layer exhibits a Schottky barrier at its grain boundaries that is high enough to block electrons, keeping the material in an insulating state overall. However, when a transient ultra-high-voltage pulse arrives, the electric field strength at the grain boundaries increases sharply, triggering Zener breakdown or tunneling of the barrier. Electrons can then cross the barrier to form a uniform volume current, rapidly leveling the potential gradient. After the pulse dissipates, the barrier recovers, and the material automatically switches back to the insulating state, achieving "reversible" adaptive protection.

[0030] For nano-zinc oxide-based varistors, the conduction threshold can be controlled by adjusting the type and total amount of doping elements (0.5 mol% to 6 mol%). Generally, increasing the content of donor dopants (such as Bi and Sb) can raise the grain boundary barrier, thereby shifting the trigger conduction voltage threshold to the higher end, thus achieving an adjustable range of 3.0 kV to 6.0 kV.

[0031] Example 1: An alkali-free enamel solder paste composition with bistable electrical response and adaptive field strength, the composition comprising a solid component and an organic carrier, wherein the organic carrier accounts for 22% of the total mass of the composition; The solid component is composed of the following components by mass percentage: 72% glass powder, 72% varistor conductive functional filler (Bi-Sb-Co-Mn co-doped nano-ZnO, D... 50 =1.5μm, surface coated with SiO2 insulating layer) 28%; The glass powder is made of oxides in the following mass percentages: BaO 24%, B2O3 30%, SiO2 13%, ZnO 8.5%, Al2O3 5%, La2O3 3.0%, Y2O3 2.0%, CeO2 2.0%, Nd2O3 1.5%, TiO2 2.0%, CaF2 3.0%, MgF2 2.5%, AlF3 2.5%; the total fluorine content in the glass powder is 5.2 wt%, and the total rare earth oxide content is 8.5 wt%. The organic carrier is composed of: 12% ethyl cellulose resin, 5% hydrogenated rosin resin, 81.5% diethylene glycol butyl ether acetate, and 1.5% anti-settling agent.

[0032] The preparation method of the above-mentioned field strength adaptive alkali-free enamel solder paste composition with bistable electrical response includes the following steps: S1. Selection and pretreatment of glass powder raw materials: Select oxide, fluoride and carbonate raw materials with a purity ≥99.5% according to the glass powder formula, and dry them at 250℃ for 3h to remove adsorbed water and crystal water, and set them aside for later use; S2. Precise weighing and mixing of glass powder: Precisely weigh each raw material according to the glass powder formula, with a total weighing accuracy of ≤0.1%; place the weighed raw materials in a zirconia ball mill jar, add zirconia grinding balls, with a ball-to-material ratio of 3:1, dry ball milling for 4 hours at a speed of 150 rpm, and then pass the mixture through a 120-mesh sieve to ensure no agglomeration. S3, Glass Powder Sealed Melting: The mixture obtained in S2 is loaded into a lidded platinum crucible or high-purity corundum crucible. The crucible lid and body are sealed with high-temperature mullite sealant. The crucible is placed in a high-temperature electric furnace and heated to 1200℃ at a rate of 10℃ / min. The temperature is held for 2.0h without stirring to avoid introducing air bubbles and impurities. After the holding period, the crucible is quickly removed to obtain a homogeneous molten glass liquid. S4. Water quenching and annealing of molten glass: The molten glass in the crucible is quickly poured into deionized water for water quenching to obtain a glass frit; the glass frit is dried at 150℃ for 2 hours, and then placed in an annealing furnace, heated to 500℃ at a rate of 2℃ / min, held for 2.0 hours, and then slowly cooled to room temperature at a rate of 1℃ / min to fully eliminate internal stress and obtain a glass frit. S5. Glass frit crushing and classification: The glass frit obtained in S4 is coarsely crushed to <5mm (jaw crusher), then placed in a planetary ball mill, using a zirconia jar and zirconia balls, with a ball-to-material ratio of 6:1, a rotation speed of 250 rpm, and grinding for 4 hours. Finally, the particle size distribution is controlled by an air classifier to obtain glass powder. The particle size distribution of the glass powder is controlled as follows: D 50 =2μm~7μm, D 10 ≥1.0μm, D 90≤18μm; defective products will be returned for re-grinding; S6. Pretreatment of varistor-conductive functional filler: Place nano zinc oxide-based varistor material or silicon carbide whiskers in a tube furnace and perform high-temperature oxidation treatment at 750°C for 60 minutes in an oxygen or air atmosphere to form a dense high-resistance oxide layer (ZnO or SiO2) on its surface. Then cool, break up, and pass through a 200-mesh sieve to obtain the pretreated varistor-conductive functional filler. The nano-zinc oxide-based varistor material is a ZnO varistor powder co-doped with Bi2O3, Co2O3, MnO2, Sb2O3, and Cr2O3, with a total doping amount of 3 mol%. S7. Mixing of solid components: Weigh the glass powder obtained in S5 and the pretreated pressure-sensitive conductive functional filler obtained in S6 according to the solid component ratio, place them in a V-type mixer or a three-dimensional motion mixer, mix for 60 minutes to ensure that the two powders are evenly dispersed to obtain mixed solid powder. S8. Preparation of organic carrier: According to the formula of organic carrier, ethyl cellulose resin, hydrogenated rosin resin, anti-settling agent and organic solvent are added in sequence to a reaction vessel equipped with a stirrer and a reflux condenser. The mixture is heated in a water bath at 75°C and stirred at a constant temperature for 2 hours until all components are completely dissolved to form a clear and transparent homogeneous organic carrier. S9. Preparation of solder paste: The mixed solid powder obtained in S7 and the organic carrier obtained in S8 are placed in a double planetary vacuum stirrer and deaerator in proportion. Under the conditions of vacuum degree ≤ -0.095MPa and rotation speed 800rpm, the mixture is stirred and mixed for 60min to fully wet the solid powder and organic carrier and form a uniform, stable, bubble-free paste, which is the bistable electrical response field strength adaptive alkali-free enamel solder paste composition. The viscosity of the solder paste composition is 80Pa·s (Brookfield HBDV-II, CP51 rotor, 25℃, 5rpm).

[0033] After screen printing the enamel solder paste obtained in this embodiment, it was sintered at 820°C for 30 minutes under nitrogen atmosphere protection to form a dense composite enamel sintered film. See [link to relevant documentation]. Figure 1 The performance test results of the composite enamel sintered film are as follows: The normal volume resistivity (25℃) is 3.2 × 10⁻⁶. 14 Ω·cm, volume resistivity at 500℃ is 7.5×10⁻⁶ Ω·cm 11 Ω·cm; the trigger conduction voltage threshold is 4.5kV (film thickness 100μm), and the conduction resistance is 380Ω; after 50 8 / 20μs lightning current wave impacts, the conduction threshold voltage change rate is <5%, and there is no breakdown degradation phenomenon; the Vickers hardness is 6.4GPa; the interfacial shear strength between the coating and the stainless steel substrate reaches 42MPa.

[0034] The above results show that the material in this embodiment fully meets the multiple stringent requirements of high-reliability scenarios such as nuclear fusion devices and ultra-high voltage converter valves for normal insulation, transient adaptive conduction, and long-term robust bonding at the interface.

[0035] Example 2: A field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response, the solid component of which is composed of the following components by mass percentage: 65% glass powder, varistor-sensitive conductive functional filler (β-SiC whiskers, average aspect ratio 12:1, D... 50 =3μm, surface treated with 800℃ oxidation) 35%; The glass powder is made of oxides in the following mass percentages: BaO 21%, B2O3 32%, SiO2 15%, ZnO 7%, Al2O3 4.5%, La2O3 3.5%, Y2O3 1.0%, CeO2 2.5%, Nd2O3 1.2%, TiO2 2.5%, CaF2 3.5%, MgF2 2.0%, AlF3 1.8%; the total fluorine content in the glass powder is 5.0 wt%, and the total rare earth oxide content is 8.2 wt%. The remaining preparation methods are the same as in Example 1.

[0036] Test results show that its trigger conduction voltage threshold is 3.8kV, conduction resistance is 620Ω, interface shear strength is 39MPa, and pulse withstand capability is excellent. It is suitable for insulation protection scenarios of power modules of rail transit traction converters with higher requirements for mechanical strength and thermal conductivity.

[0037] Example 3: A field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response, the solid component of which is composed of the following components by mass percentage: 80% glass powder, 80% varistor conductive functional filler (Bi-Mn co-doped nano-ZnO, D... 50 =2.5μm, with an Al2O3 insulating layer covering the surface (20%).

[0038] The glass powder is made of oxides in the following mass percentages: BaO 26%, B2O3 28%, SiO2 12%, ZnO 10%, Al2O3 5.5%, La2O3 2.0%, Y2O3 2.5%, CeO2 1.5%, Nd2O3 0.8%, TiO2 1.8%, CaF2 2.5%, MgF2 2.0%, AlF3 2.4%; the total fluorine content in the glass powder is 5.8 wt%, and the total rare earth oxide content is 6.8 wt%.

[0039] The remaining preparation methods are the same as in Example 1.

[0040] Test results show that its trigger voltage threshold is 5.2kV, the on-state resistance is 280Ω, and the interface shear strength is 44MPa, exhibiting higher conduction sensitivity and better interface bonding characteristics. It is particularly suitable for high-voltage modulators in medical heavy ion accelerators where response speed and long-term reliability are extremely important.

[0041] Comparative Example 1: Compared to Example 1, the B2O3 network formation is missing; This comparative example is used to investigate the effect of B2O3 deficiency in the glass network agglomerates on the overall properties of the material. The glass powder formulation does not contain any B2O3. The missing mass is made up by an equal amount of SiO2 to maintain the total mass percentage, namely BaO 24%, SiO2 43%, ZnO 8.5%, Al2O3 5%, La2O3 3.0%, Y2O3 2.0%, CeO2 2.0%, Nd2O3 1.5%, TiO2 2.0%, CaF2 3.0%, MgF2 2.5%, and AlF3 2.5%. The type and amount of varistor conductive functional filler, the proportion of organic carrier, and the preparation process are all consistent with those in Example 1.

[0042] During the preparation process, it was found that due to the lack of B2O3, a key fluxing component, the glass mixture melted incompletely at 1240℃, resulting in extremely high melt viscosity and an inability to form a homogeneous glass melt. Water quenching yielded a mixture of numerous unmelted crystalline particles and a small amount of glass phase. Even increasing the sintering temperature to 900℃ failed to achieve densification, resulting in a porous and loose sintered film. Performance tests showed that its normal volume resistivity was only 3.5 × 10⁻⁶. 10 Ω·cm, and the high-temperature resistivity is further reduced to 10. 7 It is on the order of Ω·cm and completely loses its triggering and conduction function.

[0043] This fully demonstrates that B2O3 is not only the foundation for constructing a low-melting-point, high-fluidity glass network in this invention, but also a prerequisite for achieving uniform solid solution of other functional components (rare earth elements, fluorides), and its presence is indispensable.

[0044] Comparative Example 2: Compared to Example 1, the BaO network modifier is missing; This comparative example is used to examine the effect of BaO deficiency in the core network modifier on insulation performance; The glass powder formulation does not contain any BaO. The missing mass is replaced by an equal amount of CaO, namely CaO 24%, B2O3 30%, SiO2 13%, ZnO 8.5%, Al2O3 5%, La2O3 3.0%, Y2O3 2.0%, CeO2 2.0%, Nd2O3 1.5%, TiO2 2.0%, CaF2 3.0%, MgF2 2.5%, and AlF3 2.5%. The remaining conditions are exactly the same as in Example 1.

[0045] The results show that, although Ca 2+ with Ba 2+ Both belong to alkaline earth metals, but Ca 2+ Its ionic radius is smaller, and its polarizability is much lower than that of Ba. 2+ This prevents the formation of a tightly packed glass network structure. The volume resistivity of the sintered film obtained in this comparative example decreased to 4.8 × 10⁻⁶ under normal conditions. 12 The resistivity drops sharply to 2.5 × 10⁻⁶ Ω·cm, especially at high temperatures of 500℃. 9 Its thermal expansion coefficient (Ω·cm) is insufficient to meet the minimum requirements for high-temperature insulation in high-voltage equipment. Furthermore, its coefficient of thermal expansion increases to 9.5 × 10⁻⁶. -6 At ℃, severe expansion mismatch occurs with the metal substrate, and obvious cracking appears in the coating after sintering, with an interfacial shear strength of less than 8MPa. The results show that the high polarizability heavy ion effect provided by BaO is the key to obtaining ultra-high volume resistivity in this invention, and CaO cannot achieve an equivalent substitution.

[0046] Comparative Example 3: Compared to low-fluorine content control, total fluorine <1.0wt% lacks interfacial bonding and insulation enhancement effects; This comparative example is used to systematically verify the irreplaceable role of the high fluorine content design (2.5wt%~6.5wt%) of the present invention in improving intrinsic insulation performance and enhancing interfacial bonding. The amount of fluoride added in its glass powder formulation was significantly reduced, with CaF2 adjusted to 0.3%, MgF2 to 0.2%, and AlF3 to 0.2%, resulting in a total fluorine content of approximately 0.6 wt%. The missing mass was made up by an equal amount of SiO2, while the remaining components and preparation conditions remained consistent with those in Example 1.

[0047] Test results show that when the low-fluorine sample is sintered at 820℃, the wettability of the glass melt to the nano-ZnO pressure-sensitive filler is extremely poor, and the porosity inside the sintered film is as high as 25% or more. More importantly, due to the lack of highly electronegative fluorine... - Due to the electron cloud shielding effect and cation pinning effect, its normal volume resistivity is only 1.2 × 10⁻⁶. 13The volume resistivity is more than an order of magnitude lower than that of Example 1; the volume resistivity at 500°C drops even more sharply to 8.0 × 10⁻⁶ Ω·cm. 6 Ω·cm indicates that Ba at high temperatures 2+ and Zn 2+ The migration lost F - Effective pinning. Regarding interface integration, due to F... - Due to severe deficiency, a continuous Me-Fx chemically bonded transition layer cannot be formed in situ at the interface between the molten glass and the metal substrate; the bonding relies solely on fragile mechanical interlocking, resulting in a sharp drop in interfacial shear strength to 12 MPa. After 50 thermal shock cycles from -55℃ to +125℃, large-scale peeling and flaking occurred at the coating edges; the trigger voltage threshold increased to 7.5 kV, and the on-state resistance reached as high as 1.2 × 10⁻⁶. 4 Ω has completely lost its practical value.

[0048] This fully demonstrates that significantly increasing the fluorine content in this invention is not only a means to improve the sinterability of the process, but also a core technical path to enhance intrinsic insulation performance, pin movable cations, and establish strong interfacial chemical bonds.

[0049] Comparative Example 4: Compared to Example 1, it lacks rare earth oxide co-doping; This comparative example is used to investigate the effect of the complete absence of La2O3, Y2O3, CeO2, and Nd2O3 on the density and electrical properties of the glass network; The glass powder formulation completely removes all rare earth oxides, and the missing mass is made up by SiO2 and Al2O3 in equal proportions, namely BaO 24%, B2O3 30%, SiO2 20.5%, ZnO 8.5%, Al2O3 9%, TiO2 2.0%, CaF2 3.0%, MgF2 2.5%, and AlF3 2.5%; the remaining conditions are the same as in Example 1.

[0050] Test results show that the chemical stability of the glass network structure is significantly reduced without rare earth co-doping. During sintering, the nano-ZnO varistor filler undergoes abnormal grain growth, destroying the original grain boundary barrier structure; its triggering and conduction characteristics become extremely unstable, with the conduction threshold voltage drifting by more than ±20% after three pulse impacts, and the Vickers hardness decreasing to 4.5 GPa, indicating severely insufficient mechanical strength.

[0051] This indicates that the "pinning effect" and "charge trapping effect" of rare earth elements play a decisive role in stabilizing grain boundaries, inhibiting grain growth, and ensuring pulse tolerance reliability, and are one of the key components that cannot be reduced in this invention.

[0052] Comparative Example 5: Compared to Example 1, it lacks a pressure-sensitive conductive filler; This comparative example is used to verify the material basis upon which the core function of this invention—the "bistable field strength adaptive" characteristic—is realized. The glass powder formulation is exactly the same as that in Example 1, but no nano zinc oxide varistor is added to the solid component, that is, the solid component is 100% glass powder; in order to maintain the viscosity of the solder paste, the proportion of organic carrier is increased accordingly; the rest of the preparation and testing conditions are the same as those in Example 1.

[0053] The results show that the comparative sample consistently exhibits pure insulator characteristics (volume resistivity > 10 kV) over a wide voltage range of 0–10 kV. 14 (Ω·cm) shows no current discharge or conduction at any voltage level, and has no voltage clamping or surge absorption capability. When a transient pulse exceeding 6kV is applied, the energy accumulates entirely inside the material because the conduction mechanism cannot be activated, causing the sample to undergo irreversible brittle breakdown and fragmentation.

[0054] This comparative example powerfully demonstrates from the opposite perspective that only through the synergistic effect of glass powder and pressure-sensitive filler can a bistable intelligent response mechanism of "normal high resistance - transient low resistance" be constructed, and the core technical objective of this invention cannot be achieved without either component.

[0055] Comparative Example 6: Replace the alkali-free system with the traditional Na2O-K2O alkali metal system; This comparative example is used to verify the necessity of the design baseline of the present invention, which is "free from any monovalent metal elements"; The basic glass system is replaced by the traditional sodium-calcium-silicon system instead of the barium-boron system of this invention. The specific formula is: Na2O 15%, K2O 5%, SiO2 45%, B2O3 10%, Al2O3 8%, CaO 10%, MgO 5%, TiO2 2%, without adding any rare earth elements and fluorides, and the total fluorine content is 0. The type and amount of varistor conductive functional filler (28%) and the preparation process are consistent with those in Example 1.

[0056] Test results show that although this comparative example still exhibits certain insulation properties at room temperature (volume resistivity of approximately 2 × 10⁻⁶), 13 (Ω·cm), but once the temperature rises above 300℃, Na + and K + When alkali metal ions begin to migrate long distances under the influence of an electric field, the volume resistivity drops exponentially, falling below 1×10⁻⁶ at 500℃. 6 At Ω·cm, it completely loses its insulating function; at the same time, the migration of alkali metal ions also triggers severe electrochemical corrosion, causing the grain boundary barrier of the nano ZnO filler to completely collapse, and the entire material becomes a conductor at high temperature, making it impossible to use in any high-voltage power electronic equipment.

[0057] This comparative example clearly demonstrates that completely eliminating monovalent metal elements is the absolute cornerstone for achieving ultra-high insulation performance at high temperatures in this invention, and no system containing alkali metals can reach the technical level of this invention.

[0058] Comparative Example 7: With Cl - Replace F - A comparative experiment of halide anions; This comparative example is used to examine F in this invention. - The irreplaceable nature of fluorine verifies its unique size effect and chemical activity; All CaF2, MgF2, and AlF3 in the glass powder were replaced with equimolar amounts of CaCl2, MgCl2, and AlCl3. The total halogen content (in Cl2) was determined. - The total fluorine content (calculated) is roughly the same as that in Example 1, and the other oxide components and preparation conditions are consistent with those in Example 1.

[0059] Experimental results show that Cl - The ionic radius (approximately 181 pm) is much larger than that of F. - (Approximately 133 pm), unable to be effectively embedded in the gaps between glass networks, and Cl - During high-temperature melting, it readily combines with cations in the glass network, evaporating in large quantities as HCl gas, resulting in an actual residual halogen content less than 30% of the added amount, and generating numerous interconnected bubbles within the melt. Regarding interfacial bonding, Cl... - Unable to form a stable Me-Cl chemical bond layer at the metal interface, it reacts with the metal substrate to generate loose, hygroscopic FeCl2 and NiCl2 salt corrosion products.

[0060] Performance tests showed that the interfacial shear strength of the comparative sintered film was only 18 MPa. After being placed in a humid and hot environment (85℃ / 85%RH) for 72 hours, obvious corrosion expansion appeared at the interface, and the coating blistered and peeled off over a large area. Its high-temperature volume resistivity (500℃) decreased by nearly two orders of magnitude compared with Example 1, to 9.0 × 10⁻⁶. 9 Ω·cm.

[0061] This comparative example fully demonstrates from the perspective of halogen selection that only F... - With its moderate ionic radius, highest electronegativity, and unique interfacial chemical affinity, Cl can simultaneously achieve the synergistic effects of glass network densification, mobile cation pinning, and metal-ceramic interfacial chemical bonding. - It cannot achieve an equivalent substitution with other halogen anions.

[0062] A comprehensive comparison of the above embodiments and comparative examples clearly shows that the field strength adaptive alkali-free enamel solder paste composition with bistable electrical response provided by this invention comprises interconnected and indispensable technical elements, including B2O3, BaO, high-content fluoride, rare-earth synergistic doping system, and varistor-sensitive conductive filler. In particular, fluorine, through multiple synergistic mechanisms such as enhancing intrinsic insulation through electron cloud shielding, pinning mobile cations through [BO3F] / [AlO3F] coordination, and strengthening interfacial bonding through in-situ generation of Me-Fx chemical bonding layers, constitutes the key innovative core of this invention, distinguishing it from all existing technologies. The absence or improper substitution of any single component (such as replacing BaO with CaO, B2O3 with SiO2, reducing fluorine content, or using Cl...) - Replace F - The removal of rare earth elements or fillers can lead to severe degradation in materials in terms of melting process, normal insulation performance, high-temperature stability, interfacial bonding strength, or transient adaptive conduction function. This invention, through the deep synergy of the above elements, successfully overcomes the technical challenge of balancing insulation protection and interfacial reliability under extreme electrophysiological scenarios, demonstrating significant substantial progress and extremely high industrial application value.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response, characterized in that, The solder paste composition consists of solid components and an organic carrier, with the organic carrier accounting for 15% to 30% of the total mass of the composition. The solder paste composition does not contain any monovalent metal elements. The solid component comprises glass powder and varistor-sensitive conductive filler, and is made of the following components in weight percentage: Glass powder 55%–85%, varistor-sensitive conductive functional filler 15%–45%; The glass powder is a high-fluorine-content, alkali-free barium-based rare-earth synergistic glass system, composed of the following oxides by mass percentage: BaO 18%–28%, B2O3 25%–35%, SiO2 10%–16%, ZnO 5%–11%, Al2O3 3%–7%, La2O3 1.5%–4.5%, Y2O3 0.5%–3.0%, CeO2 0.5%–3.0%, Nd2O3 0%–2.5%, TiO2 0.5%–3.0%, CaF2 1.5%–4.0%, MgF2 1.0%–3.5%, AlF3 1.0%–3.5%; The pressure-sensitive conductive filler is a nano-zinc oxide-based pressure-sensitive material or silicon carbide whiskers with surface insulation treatment, and an average particle size D. 50 The range is 0.3μm to 6μm.

2. The field strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 1, characterized in that, The solid component is made from the following components by mass percentage: 72% glass powder, 28% varistor-sensitive conductive filler; The glass powder is composed of the following oxides by mass percentage: BaO 24%, B2O3 30%, SiO2 13%, ZnO 8.5%, Al2O3 5%, La2O3 3.0%, Y2O3 2.0%, CeO2 2.0%, Nd2O3 1.5%, TiO2 2.0%, CaF2 3.0%, MgF2 2.5%, AlF3 2.5%; The pressure-sensitive conductive filler is a nano-zinc oxide co-doped with Bi, Sb, Co, and Mn, with an average particle size D. 50 It has a diameter of 1.5 μm and is covered with a SiO2 insulating layer with a thickness of 5 nm to 15 nm.

3. The field strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 1, characterized in that, The organic carrier is composed of the following components by mass percentage: Ethyl cellulose resin 8%–18%, hydrogenated rosin resin 2%–8%, organic solvent 70%–88%, anti-settling agent 0.5%–2%; The organic solvent is one or more of diethylene glycol butyl ether acetate, terpineol, and dibutyl phthalate; the anti-settling agent is at least one of hydrogenated castor oil, modified bentonite, or polyamide wax.

4. The field strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 1, characterized in that, The total fluorine content in the glass powder, calculated as F element, is 2.5wt% to 6.5wt%, and the total rare earth oxide content of La2O3+Y2O3+CeO2+Nd2O3 is 3.0wt% to 10.0wt%.

5. A field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to any one of claims 1-4, characterized in that, The sintered film performance indicators of the solder paste composition are as follows: Coefficient of linear expansion α (30℃~450℃): 6.8×10⁻⁶ -6 / ℃~8.2×10 -6 / ℃; Glass transition temperature Tg: 560℃~660℃; Normal volume resistivity test at 1kV, 25℃: ≥1×10 14 Ω·cm; High-temperature volume resistivity at 500℃: ≥5×10 11 Ω·cm; Trigger turn-on voltage threshold V_breakdown, adjustable from 3.0kV to 6.0kV for a film thickness of 100μm; On-state resistance @ 1.2 × V_breakdown: ≤ 5 × 10 2 Ω; Pulse withstand capability with 8 / 20μs lightning current wave: ≥50 impacts without breakdown or degradation; Vickers hardness: ≥6.0 GPa; Firing temperature range: 760℃~840℃; Coating / metal interface shear strength: ≥35 MPa.

6. A method for preparing a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Selection and pretreatment of glass powder raw materials: Select oxide, fluoride and carbonate raw materials with a purity ≥99.5% according to the glass powder formula, and dry them at 200℃~300℃ for 2h~4h to remove adsorbed water and crystal water, and set them aside for later use. S2. Precise weighing and mixing of glass powder: Precisely weigh each raw material according to the glass powder formula, with a total weighing accuracy of ≤0.1%; place the weighed raw materials in a zirconia ball mill jar, add zirconia grinding balls, with a ball-to-material ratio of (2.5~3.5):1, dry ball milling for 3h~5h at a speed of 100rpm~150rpm, and after mixing, pass through a 120-mesh sieve to ensure no agglomeration; S3. Sealed melting of glass powder: The mixture obtained in S2 is loaded into a lidded platinum crucible or a high-purity corundum crucible. The crucible lid and body are sealed with high-temperature mullite sealant. The crucible is placed in a high-temperature electric furnace and heated to 1160℃~1240℃ at a rate of 8℃ / min~12℃ / min. The temperature is held for 1.5h~2.5h. After the holding time is completed, the crucible is quickly removed to obtain a homogeneous molten glass liquid. S4. Water quenching and annealing of molten glass: The molten glass in the crucible is quickly poured into deionized water for water quenching to obtain a glass frit; the glass frit is dried at 120℃~180℃ for 2h~3h, and then placed in an annealing furnace, heated to 485℃~535℃ at a rate of 2℃ / min~3℃ / min, held at that temperature for 1.5h~2.5h, and then slowly cooled to room temperature at a rate of 0.5℃ / min~1℃ / min to fully eliminate internal stress and obtain a glass frit; S5. Glass frit crushing and classification: The glass frit obtained in S4 is coarsely crushed to <5mm, and then placed in a planetary ball mill. Zirconia jar and zirconia balls are used, with a ball-to-material ratio of (5~7):1, a rotation speed of 200rpm~300rpm, and grinding for 3h~6h. Finally, the particle size distribution is controlled by an air classifier to obtain glass powder. S6. Pretreatment of pressure-sensitive conductive functional filler: Commercially available or self-made nano zinc oxide-based pressure-sensitive material or silicon carbide whiskers are placed in a tube furnace and subjected to high-temperature oxidation treatment at 650℃~850℃ for 30min~90min in an oxygen or air atmosphere to form a dense high-resistance oxide layer on its surface. Then, it is cooled, broken up, and passed through a 200-mesh sieve to obtain the pretreated pressure-sensitive conductive functional filler. S7. Mixing of solid components: Weigh the glass powder obtained in S5 and the pretreated pressure-sensitive conductive functional filler obtained in S6 according to the solid component ratio, place them in a V-type mixer or a three-dimensional motion mixer, and mix for 40 min to 80 min to ensure that the two powders are evenly dispersed to obtain mixed solid powder. S8. Preparation of organic carrier: According to the formula of organic carrier, ethyl cellulose resin, hydrogenated rosin resin, anti-settling agent and organic solvent are added in sequence to a reaction vessel equipped with a stirrer and a reflux condenser. The mixture is heated in a water bath at 60℃~95℃ and stirred at a constant temperature for 1.5h~3h until all components are completely dissolved to form a clear and transparent homogeneous organic carrier. S9. Preparation of solder paste: The mixed solid powder obtained in S7 and the organic carrier obtained in S8 are placed in a double planetary vacuum stirrer and deaerator in proportion. Under the conditions of vacuum degree ≤ -0.095MPa and rotation speed of 600rpm~1200rpm, the mixture is stirred and mixed for 40min~90min to fully wet the solid powder and the organic carrier and form a uniform, stable, bubble-free paste, which is the field strength adaptive alkali-free enamel solder paste composition with bistable electrical response.

7. The method for preparing a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 6, characterized in that, The coarse crushing of the glass frit obtained in S4 to <5mm, as described in S5, is performed using a jaw crusher; the particle size distribution of the glass powder is controlled as follows: D 50 =2μm~7μm, D 10 ≥1.0μm, D 90 ≤18μm; defective products are returned for re-grinding.

8. The method for preparing a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 6, characterized in that, The nano-zinc oxide-based varistor material mentioned in S6 is a ZnO varistor powder co-doped with Bi2O3, Co2O3, MnO2, Sb2O3, and Cr2O3, with a total doping amount of 0.5mol% to 6mol.

9. The method for preparing a field-strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to claim 6, characterized in that, The viscosity of the solder paste composition described in S9 is 40 Pa·s to 180 Pa·s.

10. The application of the field strength adaptive alkali-free enamel solder paste composition with bistable electrical response according to any one of claims 1-5, characterized in that, The enamel solder paste composition is applied to the surface of the electrodes, insulating bases, or equalizing shielding rings of the electronic components to be packaged by screen printing, dispensing, or casting. After descaling, sintering, and programmed cooling processes, it forms packaged solder joints, insulating coatings, or sealing layers with field strength adaptive conduction function. It is used for insulation protection and surge protection of the feeder insulation structure of controlled nuclear fusion magnets, the housing of damping capacitors of ultra-high voltage converter valves, the high voltage modulator bracket of medical heavy ion accelerators, and the power module substrate of rail transit traction converters.